002 Public Attitudes to and Knowledge of Healthcare Guidelines, and Methods to Communicate Guideline Recommendations to Patients and the Public – A Systematic Review. (15th August 2013) - Loudon, K; Santesso, N; Callahan, M; Harbour, R; Thornton, J; McFarlane, E; Treweek, S
Abstract : Background: Improving patient versions of guidelines is one way to support an increasing role for patients in health decision making. Objectives: To evaluate evidence on the public's attitudes and knowledge of clinical practice guidelines AND what strategies have been used to communicate guideline recommendations to this group. Methods: We conducted a systematic review of public attitudes and knowledge of clinical practice guidelines to inform the development of dissemination strategies for this population. We searched health databases from 2000 to 01/2013, grey literature, and we contacted guideline producers. Two reviewers independently abstracted, coded, synthesised themes from the studies. Results: We included 25 published studies and three reports (CCPG, NICE, SIGN). There was a huge variation in the public's awareness of guidelines (12 studies) from 25–75%. The key themes to communicate guidelines (15 studies) to the public included, predictive factors (amount of education), personalisation, access to care, trustworthiness (evidence behind recommendations), and self-management. Discussion: Although there were few studies for thematic analysis there were recurrent themes. When developing patient versions, the danger could be to focus on detailed formatting instead of fundamental issues around whether patients dismiss guidelines as not applicable to their unique situation and restricts care. The results will inform work focused on the public and patients being done in EU FP7 DECIDE project. Implications: Guideline producers will need to increase the public's awareness of clinical guidelines and developing communication strategies that are clearly personally applicable, trustworthy and useful for patients and carers managing their care.